The setup and relaxation of spring upwelling in a deep, rotationally influenced lake. Issue 4 (25th December 2020) - Roberts, Derek C.; Egan, Galen C.; Forrest, Alexander L.; Largier, John L.; Bombardelli, Fabian A.; Laval, Bernard E.; Monismith, Stephen G.; Schladow, Geoffrey
Abstract: Strong and sustained winds can drive dramatic hydrodynamic responses in density‐stratified lakes, with the associated transport and mixing impacting water quality, ecosystem function, and the stratification itself. Analytical expressions offer insight into the dynamics of stratified lakes during severe wind events. However, it can be difficult to predict the aggregate response of a natural system to the superposition of hydrodynamic phenomena in the presence of complex bathymetry and when forced by variable wind patterns. Using an array of current, temperature, and water quality measurements at the upwind shore, we detail the hydrodynamic response of deep, rotationally influenced Lake Tahoe to three strong wind events during late spring. Sustained southwesterly winds in excess of 10 m s −1 drove upwelling at the upwind shore (characteristic of non‐rotational upwelling setup), with upward excursions of deep water exceeding 70 m for the strongest event. Hypolimnetic water, with elevated concentrations of chlorophyll a and nitrate, was advected toward the nearshore, but this water rapidly returned to depth with the relaxation of upwelling after the winds subsided. The relaxation of upwelling exhibited rotational influence, highlighted by an along‐shore, cyclonic front characteristic of a Kelvin wave‐driven coastal jet, with velocities exceeding 25 cm s −1 . The rotational front also produced downwelling to 100 m, transporting dissolved oxygen to depth. More complex internal wave features followed the passage of these powerful internal waves. Results emphasize the complexity of these superimposed hydrodynamic phenomena in natural systems, providing a conceptual reference for the role upwelling events may play in lake ecosystems.